Survival rate of tiger shrimp (Penaeus monodon) pre and post infected with White Spot Syndrome Virus (WSSV) fed with the addition of miana leaf extract (Coleus scutellarioides) - Febriani, Keky; Basir, Buana; Heriansah, Heriansah (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2023)
The plant species of miana (Coleus scutellariodes) has been historically recognised for its antiviral properties.  However, there is currently no scientific evidence supporting the efficacy of miana leaf extract in preventing White Spot Syndrome Virus (WSSV) in tiger prawns (Penaeus monodon) when administered via feed. This study aimed to determine the impact of including miana leaf extract in the diet on the  survival percentage of tiger prawns that have been infected with the WSSV. The study was carried out between June and August 2023 in the Laboratory of Parasite and Fish Disease and the Hatchery Laboratory of Hasanuddin University. This study employed a completely randomized experimental design consisting of five distinct treatments, each with three replicates. The experimental treatments included the control group (treatment A), where food was provided without the inclusion of miana leaf extract. Furthermore, there were four treatment groups (treatments B, C, D and E) where feed was supplemented with miana leaf extract at concentrations of 125, 250, 500, and 750 µg mg-1 feed, respectively. Rearing was performed in two phases: preinfection (25 days) and post- infection (7 days). The statistical results of the statistical on pre-WSSV infection indicated that the addition of miana leaf extract to the food resulted in survival that was not significantly different (p>0.05). The results were different post-infection, significantly (p<0.05) the shrimp fed with the addition of miana leaf extract were higher than those without the extract. Furthermore, there was a significant difference in shrimp survival between pre- and post-WSSV infection. WSSV mitigation through immunostimulants using miana leaf extract, which is inexpensive and environmentally friendly, has the potential to minimize the impact of WSSV infection.